Perancangan Manual SMK3 Berdasarkan ISO 45001:2018: Klausul 4, 5, 7, dan 10 di Universitas “X” - Steven Pringgo; I Nyoman Sutapa (Jurnal Titra, 2022)
In carrying out work or activities, accidents can occur anywhere, anytime and this is certaintly not desireable. Unsupportive workplace conditions (no personal protective equipment) can also threaten worker safety and can disrupt worker productivity. Indonesian national standardization on SNI ISO 45001:2018 creates an occupational health and safety management system that can minimize work accidents and can achieve the goals set by the organization or company in this case “X” University. Initially, “X” University did not have a policy that regulated the importance of occupational health and safety. The design of the occupational health and safety management of “X” University designed the SMK3 manual to realize safe, comfortable and healthy campus activites by creating on organizational structure that regulates human resource that will run and manage the SMK3 at “X” University to be more organized.